MUDANÇA EM VOLUME, BIOMASSA E CARBONO DO FUSTE EM UMA FLORESTA ESTACIONAL SEMIDECIDUAL DA MATA ATLÂNTICA, ES - Silva, Lucas Duarte Caldas da (2020)
Studies on changes in forests can assess the behavior of species during growth, mortality and ingrowth, as well as changes that occur in the wood volume, biomass and carbon stocks of the forest over a certain period of time. The quantification of these pr